Editorial: Regional Communications and the Role of Satellites - Campbell, Leith H. (Journal of Telecommunications and the Digital Economy, 2022)
This editorial comes in two parts: some remarks on the role of satellites for regional telecommunications; and a brief introduction to the papers in this issue.